Quartic anomalous couplings in γγ colliders - Iboli, O. J.P.; Magro, M. B.; Mercadante, P. G.; Novaes, S. F. [UNESP] (American Physical Society (APS), 1995)
We study the constraints on the vertices W+W-Zγ, W+W-γγ, and ZZγγ that can be obtained from triple-gauge-boson production at the next generation of linear e+e- colliders operating in the γγ mode. We analyze the processes γγ→W+W-V (V=Z or γ) and show that these reactions increase the potential of e+e- machines to search for anomalous four-gauge-boson interactions. © 1995 The American Physical Society.